2018
DOI: 10.25135/rnp.79.18.01.204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Antiinflammatory and Antiandrogenic Effects of Garden Cress (Lepidium sativum L.) in HaCaT cells

Abstract: Lepidium sativum L. (Brassicaceae) (Ls), garden cress, is an edible herb that is botanically related to watercress and mustard, sharing their peppery, tangy flavor and aroma. The various parts of the plant have been traditionally used for many respiratory, rheumatologic, cardiovasculary, metabolic, and gastrointestinal disorders. Several studies were performed showing its antiinflammatory, anticarcinogenic, antiproliferative as well as tissue protective effects. In all of these studies the positive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Most cells were cultured in DMEM (83.33%; n = 5) or EPI-500 (16.67%; n = 1) medium. The main characteristics related to in vitro studies are described in detail in Table S3 [ 16 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most cells were cultured in DMEM (83.33%; n = 5) or EPI-500 (16.67%; n = 1) medium. The main characteristics related to in vitro studies are described in detail in Table S3 [ 16 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study by Türkoğlu et al investigated the effects of L. sativum leaf extract on human keratinocyte cells. They showed that this extract (10 g/100 mL) altered the expression levels of several genes, including vascular endothelial growth factor (VEGF), tumor necrosis factor-alpha (TNF- α ), and 5 alpha-reductase type II (SRD5A2) in cultured keratinocyte cells [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Türkoğlu et al, the anti-inflammatory effects of L. sativum leaf extract were attributed to the lowering of TNF- α , SRD5A2, and VEGF levels. These changes could be caused by the organosulphur and phenolic compounds of the plant, which are effective in free radical scavenging [ 53 ]. In agreement with this proposal, Ahmad et al showed that L. sativum seeds reduced the inflammatory factors and TNF- α present in E. coli -stimulated mouse plasma [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies demonstrating its antiinflammatory, anticarcinogenic, antiproliferative and tissue protective effects. In all of these studies, its beneficial effect was in its antioxidant properties due to polyphenols and organosulfur compounds (Türkoğlu et al 2018). L. sativum methanol extract successfully controls diabetes, increases antioxidants and improves lipid profile (Attia et al 2019).…”
Section: Brassicaceae Familymentioning
confidence: 99%